Fire and consequential loss of commercial property in Singapore - Sho, Choon Kim (2015)
Fire and Fire Consequential Insurance are fundamental to every commercial property. In the event of fire, the policy indemnifies the company against financial loss and the consequential loss incidental thereto. Fire insurance is a major class of business and every general insurer underwrites this business in his portfolio. The purpose of the study is to analyze the trend and profitability of the fire portfolio and the effectiveness of Rate Freeze Agreement (RFA). Statistics from Insurance Commissioner Report (1980-1992) were employed to study the trend of fire business. In addition, opinions on the profitability of fire business, effectiveness of Rate Freeze Agreement and the future outlook of fire market were sought from a number of insurance companies. Sources are also obtained from literature preview. Fire Insurance is a profitable class of business. Its profitability, premium level and losses are influenced by a number of factors including infrastructure, supervision of Monetary Authority of Singapore(MAS) and proper housekeeping. From 1986, there was a decline of fire rates where keen competition and favourable claims experience were the underlying cause. There are other factors that also account for this deteriorating of fire rates that include excess capacity, low level of loyalty of buyers and cashflow underwriting. The fire rates had deteriorated to a dangerous level which drawn the attention of many general insurers in the insurance industry. Subsequently, RFA was implemented on 25 November 1986. The agreement aimed to stabilize the fire rates and secure the long term profitability of fire portfolio. There is a brief explanation on the operation of the RFA. In addition, there is an analysis of the favourable and unfavorable consequences of this agreement. From the General Insurance of Association annual report and interviewees, RF A is quite successful. However, there are certain actions that could be taken to achieve long term goals, which are recommended in the relevant chapter. There is a chapter on the future outlook of Singapore fire market where Goods and Service Tax (GST) and Fire Safety Bills ,which are tropical issues, are mentioned. Recommendations are also made to ensure the long term profitability of fire portfolio. In addition, there is a case study on the Hilton Hotel fire which provides a brief description of the event. It illustrates the application and benefits of fire and fire consequential loss insurance, and especially the every great impact of fire consequential loss. Conclusions are made and future areas of research are suggested.